Programa de ejercicio estructurado es viable y mejora la capacidad funcional en adultos mayores en Puerto Rico - Osvaldo J Hernandez Soto; Farah A Ramirez Marrero (Pensar en Movimiento)
Physical inactivity is a major risk factor affecting overall health and functional capacity among older adults. In this study we evaluated functional capacity in 22 older adults in Puerto Rico (mean age ± standard deviation = 73.3 ± 8.2 years) before, during and after eight weeks participation in a structured exercise program. Functional capacity was evaluated using a field test battery (body composition, flexibility, coordination, agility and balance, muscle endurance and cardiorespiratory endurance) validated for this population. Also, cardiorespiratory fitness (VO2max) and blood lipid levels were evaluated in a sub-sample (n = 7). A repeated measures ANOVA was used to detect changes in functional capacity before, during and after the exercise program. A paired t-test was used to evaluate changes in VO2max and lipids before and after the program. Flexibility improved significantly during the exercise program (51.6 ± 12.2 vs. 57.7 ± 8.1 cm, p=0.04) and this change was sustained at the end of the program (54.4 ± 10.2 cm). At eight weeks into the program, time in the agility and balance test improved by two seconds and muscle endurance improved by five repetitions (p<0.05 for all). No changes were observed in body composition, coordination, VO2max and lipid levels (p>0.05). These results suggest that participation in a structured exercise program for eight weeks can positively impact factors that improve movement capacity in older adults.